Technologies Serving Concrete for Economy, Durability and Sustainability - Alhassani, Yahia (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Concrete comes as the second most used material after water in the world, but it is the first used construction material especially in Middle East. World population is increasing while resources are decreasing. Therefore, construction industry needs to find a way to produce more by consuming less. Currently, concrete production results in significant carbon dioxide emissions creating an environmental hazard. On the other hand, usable sand for concrete in many countries is short in supply. Hence, science and technology need to be used at the earnest to prevent unrecoverable environmental damage associated with elevated costs. This paper describes a recently developed technology that converts desert sand into construction sand and aggregates when combined with another technology of dual mixing scheme capable of providing up to 40% of cement savings in concrete production; remarkable results are achieved. Those revolutionary, economical and environment friendly technologies are now available. We will introduce the outlines of the said technologies and then we shall present the possible applications of these technologies for efficient, sustainable and durable construction especially for the area.